Ethnomedicinal, phytochemical, pharmacological, and conservation studies of an endangered plant: the desert teak (Tecomella undulata (Sm.) Seem.) - Vats, Sharad; Bhandari, Nikkee; Ganie, Showkat Ahmad; Mir, Mushtaq Ahmad; Bashir, Nasreena (Frontiers in Pharmacology, 2025)
Tecomella undulata (Sm.) Seem, an endangered plant, is native to India, Afghanistan, Iran, Oman, and Pakistan. Traditionally, in India, the stem bark is commonly used for the treatment of leucorrhea, pain, sexual disorders, digestive disorders, eczema, and skin infections. On the other hand, in Pakistan, both the flowers and stem bark are used as a remedy for different ailments (hepatitis, jaundice, sexual disorders, anorexia, constipation, and menstrual disorders). Phenolic metabolites and their derivatives, flavonoids, steroids, alkaloids, terpenoids, fatty acids and their derivatives, and quinones are the primary bioactive metabolites identified from this plant using different spectral and chromatographic techniques. T. undulata possesses hepatoprotective, antimicrobial, analgesic, antidiabetic, antioxidant, anti-obesity, acaricidal, and miticidal activities. However, these bioactivities have been partially validated scientifically. Thus, comprehensive reports exploring the mechanism of action of plant extracts/metabolites are needed to ascertain the therapeutic effect of T. undulata. The use of the plant in Ayurvedic formulations, as a source of timber, and in a few patents highlights their commercial importance. Preliminary toxicity studies suggest that the plant is reasonably safe; however, more in-depth data from animal models and clinical studies are needed to confirm its safety. There are a few reports on the micropropagation of this endangered plant, which can be used as a conservation strategy. With the plant being included in the Red Data Book, it becomes imperative to explore its tissue culture for the sustainable production of leading bioactive metabolites. Overall, this review compiles information on the ethnomedicinal uses, bioactive metabolites, pharmacology, commercial applications, toxicity, and micropropagation of T. undulata for further exploitation of the plant as a therapeutic agent.